Isolation of oleosin and determination of oil body size in Brassica juncea (Journal of Oilseed Brassica, 2026)
Oil bodies are structural entities that store triacylglycerols (TAG) in oilseeds. Each oil body contains a matrix of triacylglycerol (TAG) surrounded by a layer of phospholipids and its associated oil body proteins. Description of oil body and its associated proteins has not been well documented in Brassica juncea unlike Arabidopsis which is a related species. In this study extraction of oil bodies (OB) was done by flotation method following which the presence and integrity of oil bodies was confirmed using compound light microscope. The size of OB ranged from 0.58 (Maya) to 1.05 μm (HB9902). The major phospholipid as profiled by TLC was phospotidylcholine. Purification of structural proteins was done by altering the time of urea (8M) treatment. The proteins isolated from the oil bodies showed multiple bands in SDS-PAGE that included oleosin protein. Downstream purification of oil body proteins was standardized to remove further unspecific bands by additional urea treatment with time of incubation 30 min, 1h and overnight at room temperature.Out of the three, overnight incubation showed less appearance of unspecific bands. A comparative study among selected genotypes was also done showing oil content to be inversely related to oil body size and positively correlated to oleosin content. Hence by manipulating the oleosin proteins, it may be possible to increase the oil content.